The Policy of Residential Plots Secretion And its results Dr. Jamal Baker Al-Sa'ady Case Study (Baghdad City) - Jamal Baqer Al-Sa'ady; Sana sata Abbas; Haidar Abd-Al-Razak Abd-Al-Razak (Iraqi Journal of Architecture and Planning, 2009)
Housing considered as a basic need for humtn being. It's provision in Iraqdepends on all society sectors. This is required a proper means and methods, and one ofthese means are the legislations and laws, The two mairs decisions, which were dealingwith the secretion of residential plots (The decision ltlo. 850 in 1979 and the decisionNo. 940 in 1987), were one of the methods used ir solving the Housing ShortageProblem in Baghdad. Also they were a reaction to the Prevailing policy which was dealtwith the providing of large residential plots,The research aims to study this policy and its results in relation with the housingdemand, the horizontal extension and the housing densit'r.The research reached to a theoretical Model shorved the existing condition of theresidential plots in each planning area, where the research had divided Baghdad city to(7a) planning area.The research showed that this policy was more legible in low-income areas, andthe area factor (mainly which is more than 400m2; w,rs considered the more effectivefactor in this policy, in order to reach the minimum area required.This policy was more effective in single family housing market in obstructingportion of housing shortage.